2021
DOI: 10.1186/s12893-021-01060-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma originating from the rectum and diagnosed after rectal perforation during the treatment of ulcerative colitis: a case report

Abstract: Background Gastrointestinal lymphomas like diffuse large B-cell lymphoma (DLBCL) are rare complications of ulcerative colitis (UC), and only a few studies have reported intestinal ulcers caused by DLBCL, which got perforated during the treatment of UC. Case presentation A 43-year-old man with severe lower abdominal pain and an 8-year history of UC was admitted in our hospital. He was diagnosed UC since 8 years and received a maintenance oral dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The perforation rate in gastrointestinal lymphoma is about 9%–22%, exceeding the rate observed in high-grade lymphomas such as DLBCL [ 7 ]. DLBCL represents a fast-growing B-cell lymphoma, histologically identified by the widespread growth of large cancerous B lymphoid cells whose nucleus size matches or surpasses the nuclei of typical histiocytes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perforation rate in gastrointestinal lymphoma is about 9%–22%, exceeding the rate observed in high-grade lymphomas such as DLBCL [ 7 ]. DLBCL represents a fast-growing B-cell lymphoma, histologically identified by the widespread growth of large cancerous B lymphoid cells whose nucleus size matches or surpasses the nuclei of typical histiocytes [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary gastrointestinal lymphoma can lead to a reduction in the mechanical integrity of the gastrointestinal wall, potentially resulting in intestinal perforation [ 7 ]. Several studies have indicated that perforation is an unfavorable prognostic indicator for individuals with high-grade lymphomas such as DLBCL [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, however, primary rectal DLBCL developed in the absence of previous or current immunomodulatory therapy for the treatment of UC. Although being extremely rare, similar cases have been reported in the literature [10, 12, 13], raising the hypothesis of alternative mechanisms contributing to the development of DLBCL in UC patients [10]. One of the possible mechanisms is overstimulation of the immune system secondary to chronic colorectal inflammation.…”
Section: Discussion/conclusionmentioning
confidence: 80%